Temperature dependence of giant tunnel magnetoresistance in epitaxial Fe/MgO/Fe magnetic tunnel junctions - Wang, S; Ward, R; Du, G; Han, X; Wang, C; Kohn, A (2008)
The temperature dependence of giant tunnel magnetoresistance (TMR) in epitaxial Fe/MgO/Fe magnetic tunnel junctions has been investigated. The resistance in the parallel configuration between the bottom (free) Fe layer and the top Fe layer, exchange biased by an IrMn antiferromagnetic layer, is nearly independent of the temperature. In contrast, in the antiparallel configuration the resistance increases with decreasing temperature, resulting in an increase in the TMR ratio from 170% at room temperature to 318% at 10 K. The dynamic conductance (G′ =dI/dV) in the parallel configuration shows flat bias voltage dependence in the range ±0.4 V, but in the antiparallel configuration it shows typical parabolic behavior as a function of bias voltage. A model, based on the temperature dependence of magnetic disorder in the two electrodes and its effect on the spin-dependent tunneling, is proposed to describe the temperature dependence of the TMR ratio and the resistance, in good agreement with our experimental data. © 2008 The American Physical Society.